Many Labs 5: Registered Replication of Albarracín et al. (2008), Experiment 7. Issue 3 (September 2020) - Corker, Katherine S.; Arnal, Jack D.; Bonfiglio, Diane B. V.; Curran, Paul G.; Chartier, Christopher R.; Chopik, William J.; Guadagno, Rosanna E.; Kimbrough, Amanda M.; Schmidt, Kathleen; Wiggins, Bradford J.
Albarracín et al. (2008, Experiment 7) tested whether priming action or inaction goals (vs. no goal) and then satisfying those goals (vs. not satisfying them) would be associated with subsequent cognitive responding. They hypothesized and found that priming action or inaction goals that were not satisfied resulted in greater or lesser responding, respectively, compared with not priming goals ( N = 98). Sonnleitner and Voracek (2015) attempted to directly replicate Albarracín et al.'s (2008) study with German participants ( N = 105). They did not find evidence for the 3 × 2 interaction or the expected main effect of task type. The current study attempted to directly replicate Albarracín et al. (2008), Experiment 7, with a larger sample of participants ( N = 1, 690) from seven colleges and universities in the United States. We also extended the study design by using a scrambled-sentence task to prime goals instead of the original task of completing word fragments, allowing us to test whether study protocol moderated any effects of interest. We did not detect moderation by protocol in the full 3 × 2 × 2 design (pseudo- r 2 = 0.05%). Results for both protocols were largely consistent with Sonnleitner and Voracek's findings (pseudo- r 2 s = 0.14% and 0.50%). We consider these results in light of recent findings concerning priming methods and discuss the robustness of action-/inaction-goal priming to the implementation of different protocols in this particular context.